2019
DOI: 10.3389/fimmu.2019.02580
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Cells Prevent the Formation of Teratomas Derived From Human Induced Pluripotent Stem Cells

Abstract: The safe utilization of induced pluripotent stem cell (iPSC) derivatives in clinical use is attributed to the complete elimination of the risk of forming teratomas after transplantation. The extent by which such a risk exists in immune-competent hosts is mostly unknown. Here, using humanized mice reconstituted with fetal hematopoietic stem cells and autologous thymus tissue (bone–liver–thymus humanized mice [Hu-BLT]) or following the adoptive transfer of peripheral blood mononuclear cells(PBMCs) (Hu-AT), we ev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…However, because most of hPSC transplantation studies are performed in immune-deficient animals or in presence of immune-suppressive drugs, the real risk of tumor formation in immune-competent hosts is mostly unknown. Recently, using multiple models of humanized mice it has been suggested that autologous hPSC-derived therapies are unlikely to form teratomas in the presence of natural killer (NK) cells [ 137 ].…”
Section: Current Challengesmentioning
confidence: 99%
“…However, because most of hPSC transplantation studies are performed in immune-deficient animals or in presence of immune-suppressive drugs, the real risk of tumor formation in immune-competent hosts is mostly unknown. Recently, using multiple models of humanized mice it has been suggested that autologous hPSC-derived therapies are unlikely to form teratomas in the presence of natural killer (NK) cells [ 137 ].…”
Section: Current Challengesmentioning
confidence: 99%
“…In addition, none of hiPSC‐MPCs or their derived myotubes were able to induce NK cell‐degranulation and/or specific cytotoxicity (Figure 3D‐G). This could be explained by the fact that hiPSC‐MPCs, in opposition to hiPSC, express high levels of HLA‐I as we have shown before 13 …”
Section: Resultsmentioning
confidence: 58%
“…The fact that MPCs were not rejected by NK cells in Hu‐AT mice cannot be explain by an insufficient number of NK cells injected. Indeed, we recently showed the injection of a similar number of NK cells was sufficient to prevent the growth of iPSC‐derived teratomas in the same model 13 …”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations